Construction of a Teaching Package on Promoting Prosocial Internet Use and Preventing Antisocial Internet Use - Ma, Hing Keung (TheScientificWorldJOURNAL, 2011)
In the construction of the teaching package on the Internet use, two major moral characters, respect and responsibility, form the core theoretical basis. The respect character consists of respect for others and self-respect while the responsibility character contains social, civil, and global responsibility. There are a total of nine units on the Internet use in the junior secondary curriculum. There are two units in Secondary One curriculum: the first unit deals with cheating behavior and privacy issues concerning the Internet, and the second one discusses the effect of excessive use of the Internet on life and study. In Secondary Two curriculum, we discuss the following social phenomena on the Internet with students: online shopping, pornographic materials on internet, and infringement of a copyright. Finally, we have designed four units on the Internet use in Secondary Three curriculum which focuses more on the relationship between the Internet use and our health. We try to answer the question on how we can use the Internet healthily and also the possibility on how it may hurt us. Similar to the second unit in Secondary One curriculum, we have designed three more units on discussing the effects of excessive use of the Internet with students. We would like to alert students that ineffective use of the Internet will hurt us mentally and physically. For illustrative purposes, two units in the Secondary One and Two curriculums are outlined in this paper.